Implementasi Peer Support Group dalam Meningkatkan Kemampuan Psychological First Aid PMR Wira Se-Kabupaten Kediri - Girianto, Pria Wahyu Romadhon; Susmiatin, Eko Arik; Furoida, Atika Ziyana (STIKES Karya Husada Kediri, 2024)
Emergency conditions could cause a person to experience mild mental disorders to severe mental disorders. PMR members had received first aid training but had not received PFA training, resulting in a lack of PFA skill when providing first aid. The use of the peer support group method was suitable for increasing PMR members' PFA abilities when providing first aid. This research aims to determine the effect of peer support groups on the psychological abilities of first aid when providing first aid to PMR Wira members throughout Kediri Regency. One-group pretest-posttest methodology without control was used in this pre-experimental study design. The result of purposive sampling obtained 30 respondents from 497 populations. The independent variable was the peer support group, with the dependent variable being the ability of PMR Wira PFA members to provide first aid. This study used a psychological first aid ability observation sheet and the Wilcoxon Signed Rank Test statistical test with α 0.05. The research result before being given the intervention was that almost all (96.7%) of the respondents had poor abilities. After being given the intervention, all (100%) respondents had good abilities. This showed an increase in scores before and after being given the intervention. Statistical analysis showed that the p-value is 0.000 ≤ α 0.05, meaning that the peer support group influences the psychological abilities of first aid when providing first aid to PMR Wira members throughout Kediri Regency. The peer support group method could improve the overall ability of respondents because it actively involves respondents during learning, it is appropriate to the characteristics of the respondent's age development, and it is in accordance with the respondent's goals. This method could not only be applied to PMR Wira members but also to the education system.